Propofol use in newborns and children: is it safe? A systematic review - Eduardo Mekitarian Filho; Mariana Barbosa Riechelmann (Elsevier, 2020)
Objectives: To determine the main indications and assess the most common adverse events with the administration of hypnotic propofol in most pediatric clinical scenarios. Sources: A systematic review of PubMed, SciELO, Cochrane, and EMBASE was performed, using filters such as a maximum of five years post-publication, and/or references or articles of importance, with emphasis on clinical trials using propofol. All articles of major relevance were blind-reviewed by both authors according to the PRISMA statement, looking for possible bias and limitations or the quality of the articles. Summary of the findings: Through the search criterion applied, 417 articles were found, and their abstracts evaluated. A total of 69 papers were thoroughly studied. Articles about propofol use in children are increasing, including in neonates, with the majority being cohort studies and clinical trials in two main scenarios: upper digestive endoscopy and magnetic resonance imaging. A huge list of adverse events has been published, but most articles considered them of low risk. Conclusions: Propofol is a hypnotic drug with a safe profile of efficacy and adverse events. Indeed, when administered by non-anesthesiologists, quick access to emergency care must be provided, especially in airway events. The use of propofol in other scenarios must be better studied, aiming to reduce the limitations of its administration by general pediatricians. Resumo: Objetivos: Determinar as principais indicações e examinar os eventos adversos mais comuns com uso do hipnótico propofol na maioria dos cenários clínicos pediátricos. Fontes: Realizada revisão sistemática da literatura nas bases de dados PubMed, Scielo, Cochrane e EMBASE, aplicando-se filtros como máximo de cinco anos de publicação e/ou referências ou publicações relevantes em outras hipóteses com enfoque em ensaios clínicos envolvendo o propofol. Todos os artigos de maior relevância foram avaliados cegamente pelos dois autores, de acordo com o PRISMA Statement, observando os riscos de vieses e qualidades ou limitações dos estudos. Resumo dos achados: Através dos mecanismos de pesquisa, 417 artigos foram encontrados e separados logo após, de acordo com os critérios de inclusão. Um total de 69 artigos foram estudados. Destacam-se a produção científica crescente sobre o propofol em crianças, incluindo recém-nascidos, sendo a grande maioria dos trabalhos coortes retrospectivos ou prospectivos, bem como ensaios clínicos com o propofol nos principais cenários: endoscopia digestiva alta e ressonância magnética. Ampla gama de eventos adversos foi citada, mas a maioria dos trabalhos não as consideraram significativas. Conclusões: O propofol apresenta um seguro perfil de eficácia e segurança. Quando administrado por médicos não-anestesistas, deve-se redobrar o cuidado para ação rápida em emergências, especialmente de vias aéreas. A aplicação do fármaco em outros contextos deve ser estudada em maior profundidade, afim de dirimir a dificuldade do uso por pediatras.